2004
DOI: 10.1002/ajmg.b.30065
|View full text |Cite
|
Sign up to set email alerts
|

Using nonword repetition to distinguish genetic and environmental influences on early literacy development: A study of 6‐year‐old twins

Abstract: This study considered whether cognitive profile could distinguish groups of children where genes or environment played a major role in influencing reading level. Same-sex twin pairs from an epidemiological study were categorized according to parental report at 4 years of age into those with low language skills and a typically developing group. A total of 132 same-sex twin pairs from the low language group and 66 from the control group were assessed at 6 years of age, to investigate heritability of reading abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 14 publications
1
35
0
1
Order By: Relevance
“…Research has shown that children with dyslexia consistently perform less well than control participants on nonword repetition tasks (Brady, Poggie, & Rapala, 1989;Catts, 1986;Hulme & Snowling, 1992;Kamhi & Catts, 1986;Snowling, 1981;van Daal & van der Leij, 1999;van der Bob & van der Pijl, 1997). Studies have also demonstrated that heritability for dyslexia is higher when the disorder is combined with a deficit in nonword repetition (Bishop, 2001;Bishop, Adams, & Norbury, 2004;Raskind, Hsu, Berninger, Thomson, & Wijsman, 2000). Finally, research suggests a link between deficits in phonological memory and phonological awareness in that both deficits may result from an inefficiency in the formation of phonological representations (Elbro, 1996;Metsala & Walley, 1998).…”
Section: Dyslexiamentioning
confidence: 99%
“…Research has shown that children with dyslexia consistently perform less well than control participants on nonword repetition tasks (Brady, Poggie, & Rapala, 1989;Catts, 1986;Hulme & Snowling, 1992;Kamhi & Catts, 1986;Snowling, 1981;van Daal & van der Leij, 1999;van der Bob & van der Pijl, 1997). Studies have also demonstrated that heritability for dyslexia is higher when the disorder is combined with a deficit in nonword repetition (Bishop, 2001;Bishop, Adams, & Norbury, 2004;Raskind, Hsu, Berninger, Thomson, & Wijsman, 2000). Finally, research suggests a link between deficits in phonological memory and phonological awareness in that both deficits may result from an inefficiency in the formation of phonological representations (Elbro, 1996;Metsala & Walley, 1998).…”
Section: Dyslexiamentioning
confidence: 99%
“…A subsequent study with a new twin sample tested this idea further [41]. A sample of 6-year-old twins was divided into one subset where both twins had normal-range scores on non-word repetition, and another subset where one or both twins were impaired on non-word repetition.…”
Section: The Importance Of the Phenotype: Clinical Categories Do Not mentioning
confidence: 99%
“…Children with SLI have an apparent deficit in phonological working memory (PWM) as exhibited by poorer repetition of non-words, particularly as the length of the non-words increases (e.g., Dollaghan & Campbell, 1998;Gathercole, 2006aGathercole, , 2006bGathercole & Baddeley, 1990;Marton & Schwartz, 2003). Several studies have indicated that this task is a reliable identifier of language impairment and of the risk for language impairment in primary school-aged (Archibald & Gathercole, 2006a) and preschool children (Bishop, Adams, & Norbury, 2004;Briscoe, Bishop, & Norbury, 2001;Dollaghan & Campbell, 1998;Gray 2003;Roy & Chiat, 2004). One explanation for the language learning difficulties of children with SLI is that PWM affects both the acquisition of new words (which demand the retention of new phonological sequences) and broader levels of language processing such as sentence comprehension that require the manipulation of phonological information (Briscoe et al, 2001).…”
Section: Phonological Working Memory and Slimentioning
confidence: 99%